NT-proB natriuretic peptide, risk factors and asymptomatic left ventricular dysfunction: Results of the SCReening Evaluation of the Evolution of New Heart Failure Study (SCREEN-HF) - McGrady, M.; Reid, Christopher; Shiel, L.; Wolfe, R.; Boffa, U.; Liew, D.; Campbell, D.; Prior, D.; Stewart, S.; Krum, H. (2013)
Background We assessed left ventricular dysfunction in a population at high risk for heart failure (HF), and explored associations between ventricular function, HF risk factors and NT-proB natriuretic peptide (NT-proBNP). Methods and results 3550 subjects at high risk for incident HF (= 60 years plus = 1 HF risk factor), but without pre-existing HF or left ventricular dysfunction, were recruited. Anthropomorphic data, medical history and blood for NT-proBNP were collected. Participants at highest risk (n = 664) (NT-proBNP highest quintile; > 30.0 pmol/L) and a sample (n = 51) from the lowest NT-proBNP quintile underwent echocardiography. Participants in the highest NT-proBNP quintile, compared to the lowest, were older (74 years vs. 67 years; p < 0.001) and more likely to have coronary artery disease, stroke or renal impairment. In the top NT-proBNP quintile (n = 664), left ventricular systolic impairment was observed in 6.6% (95% CI: 4 to 8%) of participants and was associated with male gender, coronary artery disease, hypertension and NT-proBNP. At least moderate diastolic dysfunction was observed in 24% (95% CI 20 to 27%) of participants and was associated with diabetes and NT-proBNP. In this high risk population, NT-proBNP was associated with left ventricular systolic impairment (p < 0.001) and moderate to severe diastolic dysfunction (p < 0.001) after adjustment for age, gender, coronary artery disease, diabetes, hypertension and obesity. Conclusion A high burden of ventricular dysfunction was observed in this high risk group. Combining NT-proBNP and HF risk factors may identify those with ventricular dysfunction. This would allow resources to be focused on those at greatest risk of progression to overt HF. © 2013 Elsevier Ireland Ltd.